EFFECTIVENESS OF COMBINATION DEEP BREATHING AND PROGRESSIVE MUSCLE RELAXATION TO DIMINISH ANXIETY OF THE ELDERLY WITH HYPERTENSION - Indriana Rakhmawati; Endang Banon; Omi Haryati; Nurhalimah Nurhalimah; Mia Fatma Ekasari; Andi Sari Bunga; Ace Sudrajat (Poltekkes Kemenkes Jakarta III, 2025)
The background of this study is the prevalence of the elderly aged 64-75 with hypertension in 2023 is 57.8 percent, and the number of elderly is estimated to reach 29 million of the total number of Indonesians in 2023. Hypertension can endanger the life of the elderly because it causes various serious health complications. Anxiety as one of the factors which aggravate hypertension in elderly, needs to be controlled so that complications do not occur. Deep breathing relaxation and progressive muscle relaxation are non-pharmacological interventions that can be performed to reduce anxiety. The aim of this study was to find out whether the combination of deep breathing relaxation therapy and progressive muscle relaxation can reduce anxiety in elderly with hypertension. The design of this study is a quasi-experimental one group pretest-post-test design, because it measures the anxiety level of the elderly before and after therapy. The respondents consist of 30 elderly people in the Jatiwarna Village area, who were selected by random sampling method. Anxiety data was obtained using the HARS (Hamilton Anxiety Rating Scale) questionnaire and analyzed using descriptive and dependent t-test analysis. The results of the descriptive analysis showed that 93.3 percent of the elderly had mild anxiety before the intervention and became 100 percent after the intervention. The results of the bivariate test using the dependent t-test showed a p-value: 0.00 at a sig. value of 0.05 which indicates the effect of giving both therapies on the reduction of anxiety levels in the elderly with hypertension.